Analysis of the Promotion of Language Encouragement and Sports to the Physical and Mental Health of Learners of Chinese as a Second Language - Xindan Hu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study examines the role of language encouragement and sports in boosting the physical and mental health of learners of Chinese as a second language. This paper utilized literature research, data analysis, and other approaches to investigate the factors brought about by athletics. The questionnaire results distributed to international students serve as the supporting argument. This research examines how physical exercise can improve students' physical and mental health based on the data analysis of a questionnaire survey. Kang's thesis offers some recommendations on how to assist students in enhancing their physical activity ability and intensity in middle schools, such as referring to the examination method; by adding the physical education examination to this module, guiding students will be a priority. There is an emphasis on sports. In addition, as the government and the school increase the direction of students and invest in sports facilities, students will have the time and space to participate in sports. Language encouragement and sports can effectively regulate international students' physical and mental health, boost the self-confidence of international college students, establish positive social ties, assist students in establishing a sense of mental health, and promote the healthy development of mental health.